2005
DOI: 10.1161/01.atv.0000161050.77646.68
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Mitogenic Signaling Pathways in Aortic Smooth Muscle Cells Deficient in Superoxide Dismutase Isoforms

Abstract: Objective-Reactive oxygen species (ROS) integrate cellular signaling pathways involved in aortic smooth muscle cell (SMC) proliferation and migration associated with atherosclerosis. However, the effect of subcellular localization of ROS on SMC mitogenic signaling is not yet fully understood. Methods and Results-We used superoxide dismutase (SOD)-deficient mouse aortic SMCs to address the role of subcellular ROS localization on SMC phenotype and mitogenic signaling. Compared with wild-type, a 54% decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(68 citation statements)
references
References 34 publications
(43 reference statements)
6
55
0
7
Order By: Relevance
“…Restored NOS activity would not itself be expected to stimulate peroxynitrite in the absence of oxidant stress because this is not observed in normal hearts, and if anything, BH4 appears to lower peroxynitrite in oxidant stress disorders. 31 The present data support a growing notion that ROS signaling is compartmentalized 32 and that targeting specific oxidant generators may be more efficacious than broader antioxidant scavengers. Although both Tempol and BH4 provided similar in vitro and tissue (lucigenin) antioxidant effects, their effects on hypertrophy, fibrosis, and NOS dP/dtmax indicates peak rate of pressure rise; Ees, LV end-systolic elastance (stiffness); V100, end-systolic volume at end-systolic pressure of 100 mm Hg; M SW, slope of stroke work-end-diastolic volume relationship; dP/dtmin, peak rate of pressure decline; (norm), time constant of relaxation normalized to heart rate; and PFR/EDV, peak filling rate normalized to end-diastolic volume.…”
Section: Discussionsupporting
confidence: 79%
“…Restored NOS activity would not itself be expected to stimulate peroxynitrite in the absence of oxidant stress because this is not observed in normal hearts, and if anything, BH4 appears to lower peroxynitrite in oxidant stress disorders. 31 The present data support a growing notion that ROS signaling is compartmentalized 32 and that targeting specific oxidant generators may be more efficacious than broader antioxidant scavengers. Although both Tempol and BH4 provided similar in vitro and tissue (lucigenin) antioxidant effects, their effects on hypertrophy, fibrosis, and NOS dP/dtmax indicates peak rate of pressure rise; Ees, LV end-systolic elastance (stiffness); V100, end-systolic volume at end-systolic pressure of 100 mm Hg; M SW, slope of stroke work-end-diastolic volume relationship; dP/dtmin, peak rate of pressure decline; (norm), time constant of relaxation normalized to heart rate; and PFR/EDV, peak filling rate normalized to end-diastolic volume.…”
Section: Discussionsupporting
confidence: 79%
“…Enhanced production of ROS has been described as a potential major activator of Jak/Stat signaling (33) and can occur independently of the addition of exogenous cytokines (34). This phenomenon appears to be relatively general since ROS mediate induction of Jak-2 activation in tissues such as cardiac myocytes and vascular smooth muscle cells (34 -36) as well as kidney cells (12,14,15,32).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-␥ activators may promote the regression of fatty streaks by increasing the removal of cholesterol from macrophages (29), and they may also prevent vascular remodeling (19). Furthermore, Madamanchi et al (27) reported that Cu/ZnSOD may be involved in vascular smooth muscle cell hyperplasia and hypertrophy. These data support our observation that pitavastatin may inhibit fatty streak formation and vascular remodeling more than probucol via the activation of PPAR-␥; it also appears that pitavastatin may reduce ROS by restoring Cu/ZnSOD activity in the vascular wall in cholesterol-fed rabbits.…”
Section: Discussionmentioning
confidence: 99%